HUBUNGAN POTENSIAL PEMERCEPAT TERHADAP KUAT ARUS DAN JEJARI BERKAS ELEKTRON DALAM NISBAH MUATAN LISTRIK e/m - Lanto, Muhammad Said (Universitas Islam Negeri Alauddin Makassar, 2017)
This research is about the e / m electric charge ratio with the aim of (1) to determine the relationship between accelerator potential and current strength and electron beam radius, (2) to determine the value of e / m for electron particles based on calculation results and graphs. . This research uses a cathode tube and a coil which functions to generate a magnetic field. This coil is called a Helmholtz coil (a coil that has a radius equal to the distance of the two coils). Based on the research results, it was found that (1) the greater the potential value of the accelerator, the smaller the value of the electron beam radius, and vice versa, if the smaller the potential value of the accelerator, the greater the value of the electron beam radius. whereas the acceleration potential relation to the electron current strength, if the value of the accelerator voltage is enlarged, the strength of the electron current will also be greater, and vice versa; (2) the average e / m value of the calculation result is 1.67 Ã— 1011 C / kg and the average e / m value of the graph is 1.66 Ã— 1011 C / kg. While the percent (%) difference in the value of e / m in literature with the results of calculations and graphs is 0.05% and the percent (%) of the difference in the value of e / m in calculations with the results of the graph is 0.001%.